SOSIALISASI PENCEGAHAN STUNTING SEJAK DINI PADA CALON PENGANTIN - Ernida, Yulia; Maritalia, Dewi; Rahmadani, Nurfadhilah; Zahara, Mutia; Putri, Rahmi; Jasna; Ramadani, Ana (LPPM Universitas Al Muslim, 2024)
Stunting is a growth and development problem in children that needs to be addressed seriously and involves various sectors. One of the stunting prevention that can be done as early as possible is by socializing stunting to prospective brides. This community service activity aims to make brides-to-be aware of stunting prevention since the First 1000 Days of Life (HPK). The socialization method was carried out with lectures and questions and answers at the Gandapura KUA Office to 11 pairs of prospective brides. The socialization instrument used infocus, stunting prevention material in the form of power points, leaflets and sound hackers. The socialization was carried out on October 16, 2024 from 09.00 to 11.10, starting with remarks as well as the opening of the event by the Head of the Gandapuran District KUA followed by presentation of material and questions and answers. The service team consists of lecturers and students of the Faculty of Health, Almuslim University. The results of the socialization increased the knowledge of the participants after the socialization was carried out through feedback. Conclusion: prospective brides who take part in socialization know the causes and prevention of stunting since 1000 HPK. Suggestion: it is necessary to carry out similar activities at KUA in other areas to accelerate the reduction and prevention of stunting early on.